2011
DOI: 10.1186/ar3327
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the immunogenetics of idiopathic inflammatory myopathy

Abstract: This review summarizes the previous and current literature on the immunogenetics of idiopathic inflammatory myopathy (IIM) and updates the research progress that has been made over the past decade. A substantial part of the genetic risk for developing adult- and juvenile-onset IIM lies within the major histocompatibility complex (MHC), and a tight relationship exists between individual human leukocyte antigen alleles and specific serological subtypes, which in turn dictate clinical disease phenotypes. Multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
4
26
0
Order By: Relevance
“…The relationships between MSAs and human leukocyte antigen (HLA) polymorphisms have been well recognized in the previous studies [11]. A strong association between anti-ARS antibodies and alleles of the 8.1 common ancestral haplotype has been confirmed in several idiopathic inflammatory myopathy studies in Caucasians [11,12].…”
Section: Discussionmentioning
confidence: 92%
“…The relationships between MSAs and human leukocyte antigen (HLA) polymorphisms have been well recognized in the previous studies [11]. A strong association between anti-ARS antibodies and alleles of the 8.1 common ancestral haplotype has been confirmed in several idiopathic inflammatory myopathy studies in Caucasians [11,12].…”
Section: Discussionmentioning
confidence: 92%
“…IIMs are thought to be complex genetic diseases, initiated by immune activation following specific environmental events in genetically predisposed individuals. To date, the strongest genetic association in the IIMs has consistently shown to be within the major histocompatibility complex (MHC), and candidate gene studies have identified shared genetic susceptibility with other autoimmune diseases [1]. IIM genetic research has been hampered by the rarity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…These alleles also correlated with a more severe phenotype [157]. An important result of many genetic association studies is that HLA alleles are more strongly associated with developing MSA/MAA in IIM than showing an association to traditional clinical subgroups [153].…”
Section: Pathogenesis Geneticsmentioning
confidence: 99%
“…However, shared HLA-susceptibility between ethnic groups have also been found, which indicates that there may be an affinity to common antigenic peptides [153]. Studies done on polymorphisms in the HLA-region in Caucasians, have shown an overrepresentation of HLA-DR B1*0301 [154].…”
Section: Pathogenesis Geneticsmentioning
confidence: 99%
See 1 more Smart Citation